Entre construction territoriale et constitution ontologique de l’habitant : Introduction épistémologique aux apports de la phénoménologie au concept d’habiter - André-Frédéric Hoyaux (Cybergeo, 2002)
The aim of this paper is to discuss the dwelling concept from contemporary propositions of geographers and philosophers working on phenomenology, and then to state the pragmatic, epistemological and conceptual implications which ensue for the geography dealing with the evolution of inhabitants’ territories.